Far right political stances: the same trend in Georgia? - Tabatadze, Sandro (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with the emerging far right movements in Georgia, where the growing Europeanization process is taking place. Therefore, it aims to determine how relevant the European-experienced understanding of the far right with the similar movement political positions is. The article presents the stances of the members of far right movements (Georgian March, Anti-liberals, Georgian National Unity and Edelweiss) on foreign and identity policy and different socio-ethical issues, also assessed the neo-populist manner and belief in supremacy of the law. The conclusion summarizes the major characteristics of these far right movements in comparative way.
Keywords: political positions; far right; Georgian politics; political movements